Heterosexual Anal Intercourse: A Neglected Risk Factor for HIV?. (24th December 2012) - Baggaley, Rebecca F.; Dimitrov, Dobromir; Owen, Branwen N.; Pickles, Michael; Butler, Ailsa R.; Masse, Ben; Boily, Marie‐Claude
Abstract : Heterosexual anal intercourse confers a much greater risk of HIV transmission than vaginal intercourse, yet its contribution to heterosexual HIV epidemics has been under researched. In this article we review the current state of knowledge of heterosexual anal intercourse practice worldwide and identify the information required to assess its role in HIV transmission within heterosexual populations, including input measures required to inform mathematical models. We then discuss the evidence relating anal intercourse and HIV with sexual violence.